Organic farmers face persistent barriers to adopting diversification practices in California's Central Coast. Issue 8 (14th September 2022) - Carlisle, Liz; Esquivel, Kenzo; Baur, Patrick; Ichikawa, Nina F.; Olimpi, Elissa M.; Ory, Joanna; Waterhouse, Hannah; Iles, Alastair; Karp, Daniel S.; Kremen, Claire; Bowles, Timothy M.
ABSTRACT: In the face of myriad environmental challenges associated with industrial agriculture, some farmers and researchers have looked to diversified farming systems as a promising alternative. Despite well-documented ecological benefits, diversification practices remain rare in many regions of the U.S, even amongst organic farmers. Our study focuses on organic farmers in the Central Coast region of California, an area that has played a crucial role in the rise of organic agriculture over the last several decades. Through 20 interviews with farmers who all grow lettuce and 8 interviews with technical assistance providers, we investigate the persistent barriers that growers in this region face in adopting diversification practices including cover cropping, compost application, crop rotation, insectary strips, and hedgerows. We find that high land rents, the predominance of short-term leases, stringent food safety standards, and other supply chain pressures significantly hamper the adoption of diversification practices. In order to surmount these barriers and increase adoption, solutions must be pursued at three interconnected levels: innovation at the farm level, and policy change at the technical and structural levels. Locally-informed, integrated, and innovative policies across these three levels must be explored to support the creation of a more resilient, sustainable, and equitable food system.